Analysis of Mathematical Reflective Thinking Skills in Solving Problems in Terms of Gender Differences - Putriani, Fini May; Purnomo, Yoppy Wahyu (Universitas Pendidikan Mandalika, 2025)
This study aims to analyze the ability to think reflectively in problem solving from a gender perspective. The approach used in this study was qualitative descriptive with the aim of describing in depth the differences in reflective thinking patterns between men and women. Data were collected through in-depth interviews and participatory observations involving Yogyakarta State Elementary School students as participants. The data obtained from the tests and interviews analyzed using qualitative descriptive analysis. The results show that women tend to use a more holistic reflective thinking approach that involves evaluating social and emotional impacts and considering long-term solutions. In contrast, men tend to use a more pragmatic approach, focusing on quick and efficient solutions and relying on personal experience in problem solving. These findings showed that there were significant differences between men and women in how they think reflectively, which can affect how they solve problems. Therefore, this study suggests that a more inclusive learning approach be designed to accommodate these differences, in order to improve reflective thinking skills in both genders.